Comparison of Treatment Methods for Syndesmotic Injuries With Posterior Tibiofibular Ligament Ruptures: A Cadaveric Biomechanical Study. Issue 9 (9th September 2022) - Takahashi, Katsunori; Teramoto, Atsushi; Murahashi, Yasutaka; Nabeki, Shogo; Shiwaku, Kousuke; Kamiya, Tomoaki; Watanabe, Kota; Yamashita, Toshihiko
Background: Studies on ankle syndesmosis have focused on anterior inferior tibiofibular ligament (AITFL) and interosseous membrane injuries; however, the characteristics of posterior inferior tibiofibular ligament (PITFL) ruptures remain unclear. Purpose/Hypothesis: This study evaluated the biomechanical characteristics of syndesmotic instability caused by PITFL injury and compared various treatment methods. We hypothesized that PITFL injury would lead to syndesmotic internal rotational instability and that the stability would be restored with suture tape (ST) PITFL augmentation. Study Design: Controlled laboratory study. Methods: Ten uninjured fresh-frozen cadaveric leg specimens were tested via forces applied to the external and internal rotation of the ankle joint. The fibular rotational angle (FRA) related to the tibia, anterior tibiofibular diastasis (aTFD), and posterior tibiofibular diastasis (pTFD) were measured using a magnetic tracking system. Six models were created: (1) intact, (2) AITFL injury; (3) AITFL + PITFL injury; (4) suture button (SB) fixation; (5) SB + anterior ST (aST) fixation; and (6) SB + aST + posterior ST fixation. The FRA, aTFD, and pTFD were statistically compared between the intact ankle and each injury or fixation model. Results: In the intact state, the changes in FRA and aTFD were 1.09° and 0.33 mm when external rotation force was applied and were 0.57° and 0.41 mm when internal rotation force was applied. In the AITFL injury model, the changes in FRA and aTFD were 2.38° and 1.51 mm when external rotation force was applied, which were significantly greater versus intact ( P = .032 and .008, respectively). In the AITFL + PITFL injury model, the changes in FRA and pTFD were 2.12° and 1.02 mm when internal rotation force was applied, which were significantly greater versus intact ( P = .007 and .003, respectively). In the SB fixation model, the change in FRA was 2.98° when external rotation force was applied, which was significantly higher compared with intact ( P < .001). There were no significant differences between the SB + aST fixation model and the intact state on any measurement. Conclusion: PITFL injury significantly increased syndesmotic instability when internal rotation force was applied. SB + aST fixation was effective in restoring syndesmotic stability. Clinical Relevance: These results suggest that SB + aST fixation is sufficient for treating severe syndesmotic injury with PITFL rupture.